Research on the Influence of Groundwater in Coastal Areas on the Stress and Deformation Characteristics of Integrated Pipe Gallery - Yuanyuan Tian; Qingbiao Wang; Zhongjing Hu; Shuo Yang; Chuanxiong Peng; Xu Zhang; Zhongying Li; Xugang Wang (Geofluids)
With the high demand for basic resources such as electricity, communication, water supply, and gas in cities, most cities in my country are vigorously developing underground integrated pipe gallery. When constructing pipe gallery in coastal areas, it is necessary to consider the impact of groundwater level on structural calculations. There is still a lack of systematic research in domestic and foreign literature. Relying on the Qingdao West Coast New Area Project, this paper uses a combination of laboratory tests and MIDAS GTS/NX numerical simulation to study the influence of groundwater in the coastal area on the stress and deformation characteristics of the integrated pipe gallery. The results show that (1) the Mises stress on the roof and bottom of the integrated pipe gallery increases continuously with the rise of the groundwater level. Due to the effect of the effective stress, the Mises stress on the side wall shows a decreasing trend. (2) Due to the influence of the construction form of the cross-section interface, the maximum principal stress of each part of the M side is always smaller than that of the N side; with the continuous increase of groundwater level, the maximum principal stress at each part of the N and M sides of the pipe gallery structure joint gradually increases. (3) The overall structure of the pipe gallery floats up. Under the action of the buoyancy force, the bottom plate moves upward, and the surface displacement rises continuously with the rise of the groundwater level. (4) When the groundwater depth is the same, the analysis of the test results and the numerical simulation calculation results are basically consistent, which further verifies the validity of the numerical simulation calculation and has reference value. (5) The engineering example shows that in order to reduce the service life of the integrated pipe gallery, the impact of groundwater on the integrated pipe gallery cannot be ignored.